The Nutcracker by Peter Wright after Lev Ivanov, music by Tchaikovsky Marianela Nuñez (Sugar Plum Fairy), Vadim Muntagirov (The Prince), Anna Rose O'Sullivan (Clara), Marcelino Sambé (Hans-Peter / The Nutcracker) -- The Royal Ballet - Ivanov, Lev (Royal Opera House Covent Garden Foundation, 2018)
Choreographer Peter Wright first staged The Nutcracker, based on the iconic 1892 original by Lev Ivanov and Marius Petipa, in 1984 with the Royal Ballet. It has since become every bit as much a holiday staple as eggnog, cookies, and tinsel, enchanting audiences year after year for nearly four decades--and you would be hard-pressed to find a more dazzling production than this pristine 2018 recording by the Royal Ballet at Covent Garden. The magic of Tchaikovsky's beloved score is captured by artists of the highest calibre: Marianela Núñez as "a Sugar Plum Fairy of radiant warmth and grandeur" (The Independent), Vadim Muntagirov as the Prince, Marcelino Sambé as the Nutcracker, Gary Avis as Drosselmeyer, Anna Rose O'Sullivan as Clara, and a huge cast of world-class talent complement vivid designs by Julia Trevelyan Oman, elegant costumes, and spellbinding stage effects. An opulent treat for the senses for audiences of all ages, this very special Nutcracker is sure to earn a place in your holiday rotation for years to come....
Keywords: ballet; Internet videos